2009
DOI: 10.1002/mc.20510
|View full text |Cite
|
Sign up to set email alerts
|

Correlated downregulation of estrogen receptor beta and the circadian clock gene Per1 in human colorectal cancer

Abstract: There is a growing body of evidence that disturbed circadian clock gene expression is associated with tumor development and tumor progression. Based on our initial experiments demonstrating decreased period 1 (Per1) expression in colon cancer, we evaluated clock gene and estrogen receptor (ER) alpha/beta expression in colon cancer cells of primary colorectal tumors and adjacent normal colon mucosa (NM) by real-time RT-PCR. Analysis of gene expression in G(2) and G(3) colorectal tumors revealed a decrease of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 35 publications
3
59
0
1
Order By: Relevance
“…Other groups have shown that ERbKO mice are more susceptible to inflammation-associated colon cancer than the WT mice (Saleiro et al 2012). Clinical and experimental models of colonic carcinogenesis have suggested that the protein expression of ERb decreases as the tissues progress from a normal colonic epithelial to a malignant state (Konstantinopoulos et al 2003, Castiglione et al 2008, Di Leo et al 2008, Mostafaie et al 2009). In fact, humans with colon tumors not expressing ERb are likely to be in more advanced stages of cancer and have a higher risk for death compared with those with tumors in which ERb is present (Rudolph et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have shown that ERbKO mice are more susceptible to inflammation-associated colon cancer than the WT mice (Saleiro et al 2012). Clinical and experimental models of colonic carcinogenesis have suggested that the protein expression of ERb decreases as the tissues progress from a normal colonic epithelial to a malignant state (Konstantinopoulos et al 2003, Castiglione et al 2008, Di Leo et al 2008, Mostafaie et al 2009). In fact, humans with colon tumors not expressing ERb are likely to be in more advanced stages of cancer and have a higher risk for death compared with those with tumors in which ERb is present (Rudolph et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, clock genes have begun to be discovered as key regulators of several diverse diseases, including cancer and diabetes (Krugluger et al, 2007;Mostafaie et al, 2009;Marcheva et al, 2010;Xia et al, 2010;Shimba clock Genes show circadian rhythms in salivary Glands et al, 2011). Saliva plays numerous protective roles for oral tissues maintenance (Mandel, 1989;Dowd, 1999).…”
Section: Introduction Tmentioning
confidence: 99%
“…Thus, several reports have demonstrated the reduced expression of Period genes in sporadic and familial breast tumors 65 and hepatocellular carcinoma, 66 and downregulation of Per1 (but not Per2) in colorectal tumors. 67 Some of these changes in expression occur through epigenetic mechanisms. Methylation of the promoter regions of hPer1, hPer2, and hPer3 have been observed in breast cancer, 68 whereas hPer1, hPer2 and hCry1 promoters were hypermethylated in endometrial cancers.…”
Section: The Circadian Clock and Carcinogenesismentioning
confidence: 99%